Geriatric Nutritional Risk Index is a risk factor for long‐term decreases in patient‐reported outcome measures following total knee arthroplasty - Yasuhiko Kokubu; Shinya Kawahara; Satoshi Hamai; Yukio Akasaki; Taishi Sato; Toshiki Konishi; Takahiro Inoue; Yasuharu Nakashima (Journal of Experimental Orthopaedics)
Abstract Purpose Total knee arthroplasty (TKA) is an effective treatment for alleviating pain and improving function in patients with end‐stage knee osteoarthritis. However, factors influencing long‐term patient‐reported outcome measures (PROMs) remain underexplored. This study aimed to evaluate the relationship between preoperative nutritional status, specifically the Geriatric Nutritional Risk Index (GNRI), and the long‐term decline in PROMs following TKA. Methods We conducted a retrospective cohort study including patients who underwent TKA between 2000 and 2009. PROMs were assessed using the Knee Society Score (KSS) at two time points: an initial evaluation in 2012 (median postoperative 4 years) and a follow‐up in 2023 (median 13 years). Preoperative GNRI, body mass index (BMI), and other demographic and clinical data were collected from medical records. Statistical analysis included paired t‐tests and multivariate logistic regression to identify independent risk factors for long‐term decline in KSS scores. Results A total of 75 patients completed follow‐up assessments. Over the 11‐year follow‐up period, there was a significant decrease in the KSS functional activity scores (p < 0.001), with 47 patients experiencing a decline exceeding the minimal clinically important difference. A multivariate analysis revealed low preoperative GNRI (p = 0.0043) as a significant risk factor for long‐term decline in PROMs. Conclusion Preoperative malnutrition, as indicated by a low GNRI, is a significant risk factor for long‐term decline in functional outcomes following TKA. These findings highlight the importance of preoperative nutritional interventions and rehabilitation for improving the long‐term outcomes of patients undergoing TKA. Level of Evidence Level III, retrospective cohort study.